If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -5) + 6(2x + 6) = 0 Reorder the terms: 2(-5 + 2x) + 6(2x + 6) = 0 (-5 * 2 + 2x * 2) + 6(2x + 6) = 0 (-10 + 4x) + 6(2x + 6) = 0 Reorder the terms: -10 + 4x + 6(6 + 2x) = 0 -10 + 4x + (6 * 6 + 2x * 6) = 0 -10 + 4x + (36 + 12x) = 0 Reorder the terms: -10 + 36 + 4x + 12x = 0 Combine like terms: -10 + 36 = 26 26 + 4x + 12x = 0 Combine like terms: 4x + 12x = 16x 26 + 16x = 0 Solving 26 + 16x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 16x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 16x = 0 + -26 16x = 0 + -26 Combine like terms: 0 + -26 = -26 16x = -26 Divide each side by '16'. x = -1.625 Simplifying x = -1.625
| 9m-26=36 | | 25x^2+4y^2-6=0 | | f(0)=2(2x-5)+6(2x+6) | | 1/3*6= | | z+-40=36 | | 23-2(3+4)= | | 2(3x-1)-2x=7x+3 | | 3x+3=3x+15-5 | | 4+2X=10-4X | | 37x*0.6=77.7 | | Xy-3y-y=0 | | 2(5-8x)-5=5(2x+1) | | x^3+0x^2-3x+2=0 | | 14n=13a-11 | | w+-48=-23 | | Tn=2(3n-2) | | x^2+8*x-180=0 | | 0.08x+1.72=0.06x+1.68 | | 11in+3in=x | | -5(2x-1)+6=21 | | 3x+1/5=2x/3 | | 0.6r=-72 | | 2(pi)+d=5(pi) | | 1+r+r^2+r^3+r^4=0 | | 10=50x+10x | | ln(x)+ln(2)=ln(14) | | 9x+14-8x=-3-10 | | (16+3x)8+(X-11)3=21 | | 15+3x=24 | | 11y^2+3=0 | | 5x-53=2 | | 61y=30(2y+14) |